FORMULATION AND CHARACTERIZATION OF ODT USING DIFFERENT CO-PROCESS CONTAINING DACLATSVIR: IN VITRO AND IN VIVO PHARMACOKINETICS STUDY ON HEALTHY VOLUNTEERS FOR HEPATITIS C TREATMENT - ABOUHUSSEIN, DALIA; TEAIMA, MAHMOUD H.; AL-NUSEIRAT, ADI; BADARY, OSAMA; EL-NABARAWI, MOHAMED A.; EL-MONEM, REHAB ABD (International Journal of Applied Pharmaceutics, 2022)
Objective: This study aimed to prepare and evaluate oral disintegrating tablets (ODTs) of Daclatasvir dihydrochloride (DCV) using different co-processed excipients to enhance drug dissolution and improve oral bioavailability for the treatment of hepatitis C infection. Methods: Ten Daclatasvir-ODTs formulae were prepared using co-processed excipients via direct compression. The prepared formulae were evaluated according to taste masking, weight variation, thickness, friability, hardness, drug content, and wetting time. In vitro disintegration time, in vivo disintegration time, and in vitro dissolution tests were also evaluated and taken as parameters for the selection of the best formula. The selected best formula was subjected to an in vivo study on volunteers and compared to a marketed product. Results: All DCV-ODTs had acceptable physical properties in accordance with pharmacopeial standards. DCV-ODTs prepared with Pharmaburst® (F10) recorded the shortest wetting time (14±0.08s), fastest in vitro disintegration time (46±0.16s), shortest in vivo disintegration time (27±0.16s), and attained the fastest onset of dissolution (94.3±0.03 %) at 5 min to all other excipients and has been identified as the best formula. The in vivo pharmacokinetic study showed that the Pharmaburst-based formula has a significant Cmax increase of (2.17±0.28 μg/ml) compared to (1.42±0.59) for the marketed product and a significant decrease of Tmax to 60 min instead of 110 min for the marketed product. Conclusion: The in vivo pharmacokinetic study in humans showed that the ODTs was found to be appropriate for delivery of Daclatasvir with a faster drug absorption rate when compared to the marketed products with applicable taste related to the nature of dosage form.